Integrating zakat institutions into the mainstream economy: evidence from Malaysia / Nur Zehan Khairi, Abd Halim Mohd Noor and Nor Azizah Mohammad Amio - Khairi, Nur Zehan; Mohd Noor, Abd Halim; Mohammad Amio, Nor Azizah (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Zakat is a significant tool in economic growth whereby zakat acts as poverty eradication instrument, income redistributive device and a stabilization mechanism. Zakat is also recognized as a pioneer instrument of the world welfare system in human history. Zakat institutions play an important role as a supplement to the government's effort in eradicating poverty. Despite its significant role in the economy, zakat institutions in Malaysia have not reached its full potential yet. Zakat institutions have undergone several developments to improve its performance among them through corporatization of collection and distribution units. This contributes to the integration of zakat into the mainstream economy. This study presents the development of zakat institutions and identifies various phases of its integration into the economy. Despite the development, more effort are needed to improve the efficiency of zakat institutions.